Aqueous zinc ion battery electrolyte, preparation method thereof and aqueous zinc ion battery

By using trace amounts of phthalaldehyde to construct the electrode interface layer in the aqueous zinc ion battery, the problems of side reactions and zinc dendrites in the zinc ion battery are solved, and the ultra-long cycle stability of the electrolyte and the corrosion resistance of the zinc negative electrode are achieved. Performance reduces the cost of electrolyte.

CN119275385APending Publication Date: 2025-01-07UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699239.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The aqueous zinc ion battery has side reactions and zinc dendrites in the weakly acidic zinc salt aqueous solution, resulting in safety hazards and device failure. In the prior art, additives affect the characteristics of the electrolyte and are costly.

Method used

The trace amount of phthalaldehyde is used as an additive to build a stable molecular aggregation electrode interface layer to inhibit the uneven deposition and side reaction of zinc ions and improve the circulation stability of the electrolyte.

Benefits of technology

The uniform and dense deposition of zinc ions is achieved, which significantly reduces side reactions, improves the ultra-long cycle stability of the electrolyte and the corrosion resistance of the zinc negative electrode, and reduces the cost of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005153051320000011
    Figure HDA0005153051320000011
  • Figure HDA0005153051320000012
    Figure HDA0005153051320000012
  • Figure HDA0005153051320000021
    Figure HDA0005153051320000021
Patent Text Reader

Abstract

The invention discloses an aqueous zinc ion battery electrolyte, a preparation method thereof and an aqueous zinc ion battery, and belongs to the technical field of new energy. The aqueous zinc ion battery electrolyte comprises phthalic dicarboxaldehyde and a zinc salt. The addition of the o-phthalaldehyde does not change the property of the electrolyte, the cycle stability of the aqueous zinc ion battery electrolyte is improved by modifying the interface of the zinc negative electrode, and the zinc negative electrode has better corrosion resistance in the aqueous zinc ion battery electrolyte. In addition, the battery prepared from the aqueous zinc ion battery electrolyte has good cycling stability, high electrochemical reversibility and durability. The method has important guiding significance for further development and application of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to an aqueous zinc ion battery electrolyte, a preparation method thereof, and an aqueous zinc ion battery. Background Art

[0002] In the context of the era of "carbon peak and carbon neutrality" and the development trend of smart grids, the development of efficient energy storage devices is an inevitable trend. With its multi-dimensional advantages such as high safety, low cost, and easy operation, aqueous zinc-ion batteries are considered to be the next generation of new battery technology. Usually, aqueous zinc-ion batteries are composed of metallic zinc as the negative electrode, zinc salt aqueous solution as the electrolyte, and metal oxides and other materials as the positive electrode. Among them, metallic zinc has a high theoretical specific capacity (820mA hg -1 ), suitable redox potential (-0.76 V relative to standard hydrogen electrode), abundant reserves and good compatibility with aqueous solutions make aqueous zinc-ion batteries suitable for large-scale energy storage.

[0003] However, the metal zinc negative electrode has serious side reactions in weakly acidic zinc salt aqueous solutions, including but not limited to hydrogen production, surface corrosion, passivation, and the production of basic zinc salts. In addition, the uneven deposition of zinc ions will lead to the formation of zinc dendrites, resulting in serious protrusions that pierce the diaphragm and ultimately lead to the failure of the entire device. At the same time, the occurrence of side reactions and the generation of zinc dendrites complement and promote each other, making the intrinsically safe aqueous zinc ion battery also face safety hazards such as gas production and electrolyte leakage.

[0004] Constructing an electrode / electrolyte interface layer on the surface of the zinc negative electrode by in-situ / ex-situ methods can effectively inhibit side reactions and the formation of zinc dendrites, thereby improving its cycle stability. Among the many methods for constructing electrode / electrolyte interface layers, electrolyte engineering has the advantages of simplicity, easy operation and high efficiency. However, in the prior art, the introduction of many additives will significantly affect the properties of the electrolyte while constructing the electrode / electrolyte interface layer, such as solvation structure, hydrogen bonding and increased viscosity. In addition, the use of high concentrations of expensive additives will also lead to an increase in the cost of the electrolyte. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide an aqueous zinc ion battery electrolyte and a preparation method thereof and an aqueous zinc ion battery. The aqueous zinc ion battery electrolyte makes the deposition of zinc ions more uniform and dense, and significantly reduces the side reaction with water, thereby achieving ultra-long cycle stability of the electrolyte system.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The invention provides an aqueous zinc ion battery electrolyte comprising o-phthalaldehyde and a zinc salt.

[0008] The o-phthalaldehyde does not participate in the solvation structure of zinc ions and does not change the properties of the electrolyte. It only improves the comprehensive performance of the aqueous zinc ion battery electrolyte by modifying the zinc negative electrode interface. In addition, o-phthalaldehyde is relatively cheap and has a wide range of sources.

[0009] The aqueous zinc ion battery electrolyte of the present invention uses a trace amount of additives to enable the electrolyte to construct a stable molecular aggregation electrode interface layer (also known as zinc negative electrode OPA enrichment interface) on the surface of the zinc negative electrode without significantly increasing the cost or changing the properties of the electrolyte, thereby inducing uniform and dense deposition of zinc ions and inhibiting the occurrence of side reactions, and finally achieving ultra-long cycle stability of the aqueous zinc ion battery electrolyte.

[0010] The above-mentioned o-phthalaldehyde additive enables the aqueous zinc ion electrolyte to have a higher corrosion potential and a smaller corrosion current, so that the zinc negative electrode has better corrosion resistance in the electrolyte.

[0011] The above-mentioned o-phthalaldehyde additive makes the zinc ions in the aqueous zinc ion electrolyte deposit uniformly and densely without protrusions or dendrites. In addition, a dense and flat layered structure is formed on the surface of the zinc negative electrode.

[0012] Preferably, the concentration of o-phthalaldehyde in the battery electrolyte is 1-20 mmol / L, more preferably 1-10 mmol / L. In some specific embodiments of the present invention, it is preferably 1 mmol / L, 3 mmol / L, 5 mmol / L or 10 mmol / L.

[0013] Preferably, the concentration of the zinc salt in the battery electrolyte is 1-3 mol / L. In some specific embodiments of the present invention, the concentration of the zinc salt in the battery electrolyte is preferably 1 mol / L, 2 mol / L or 3 mol / L.

[0014] Preferably, the zinc salt is selected from one or more of zinc sulfate, zinc acetate, zinc perchlorate and zinc trifluoromethanesulfonate; more preferably zinc sulfate.

[0015] Preferably, the electrolyte also includes deionized water.

[0016] The present invention also provides a method for preparing the aqueous zinc ion battery electrolyte, which comprises uniformly mixing an aqueous solution of o-phthalaldehyde and a zinc salt to obtain the aqueous zinc ion battery electrolyte.

[0017] Preferably, the mixing is selected from ultrasonic mixing;

[0018] Preferably, the power of the ultrasonic mixing is 200-400W;

[0019] Preferably, the ultrasonic mixing time is 30-100 min.

[0020] The present invention also provides an aqueous zinc ion battery, comprising the aqueous zinc ion battery electrolyte or the aqueous zinc ion battery electrolyte prepared by the above preparation method.

[0021] The zinc negative electrode OPA-enriched interface constructed by the aqueous zinc ion electrolyte described in the present invention enables the aqueous zinc ion battery to have good cycle stability, high electrochemical reversibility and durability.

[0022] Furthermore, due to the addition of o-phthalaldehyde, the aqueous zinc ion electrolyte of the present invention can make the battery more reversible, thereby causing the zinc grains in the zinc ion deposition process to be more uniform and refined.

[0023] In addition, the aqueous zinc ion battery using the electrolyte of the present invention has a high -1 After 1000 cycles at a current density of , the battery capacity retention rate is high, maintaining at 233.5mA hg -1 .

[0024] Preferably, the aqueous zinc ion battery further comprises an ammonium ion intercalated vanadium pentoxide positive electrode, a metallic zinc negative electrode and a glass fiber separator.

[0025] The preparation of the aqueous zinc ion battery comprises the following steps:

[0026] (1) mixing active materials NVO, super activated carbon, carbon nanotubes and polyvinylidene fluoride (PVDF) with NMP solvent to obtain a slurry;

[0027] (2) uniformly coating the slurry on a stainless steel mesh current collector and drying to obtain an NVO cathode electrode sheet;

[0028] (3) In a CR2032 button cell configuration, a complete cell was assembled using an NVO cathode electrode sheet, a zinc anode, and a GF / D glass fiber separator.

[0029] In the step (1), the mass ratio of the active materials NVO, super activated carbon, carbon nanotubes and polyvinylidene fluoride (PVDF) is preferably 7:1.5:0.5:1.

[0030] The drying in step (2) is preferably carried out at 100° C. for 12 hours.

[0031] The present invention also provides the application of the aqueous zinc ion battery in new energy vehicle power batteries, fixed energy storage fields, and 3C consumer electronic products.

[0032] Compared with the prior art, the aqueous zinc ion battery electrolyte provided by the present invention comprises o-phthalaldehyde and zinc salt. The addition of the o-phthalaldehyde does not change the electrolyte properties, and the cycle stability of the aqueous zinc ion battery electrolyte is improved by modifying the zinc negative electrode interface, and the zinc negative electrode has better corrosion resistance in the aqueous zinc ion battery electrolyte. In addition, the battery prepared by the aqueous zinc ion battery electrolyte of the present invention has good cycle stability, high electrochemical reversibility and durability. This has important guiding significance for the further development and application of aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the EXAFS (extended X-ray absorption fine structure) image in test example 1;

[0034] Figure 2 This is the surface differential capacitance diagram of test case 2;

[0035] Figure 3 It is the Tafel curve diagram of test example 3;

[0036] Figure 4 This is the cross-sectional evolution diagram of the zinc negative electrode of Test Example 4;

[0037] Figure 5 This is a scanning electron microscope image (SEM) of the surface of the zinc sheet after 100 cycles of Zn / / Zn in Test Example 5;

[0038] Figure 6 The Zn / / Zn symmetric cell of Test Example 6 at 1 mA cm -2 , 1mA h cm -2 Cyclic stability test diagram under the conditions of

[0039] Figure 7 The Zn / / Zn symmetric cell of Test Example 7 at 1 mA cm -2 , 1mA h cm -2 Cyclic stability test diagram under the conditions of

[0040] Figure 8 A reversibility test diagram of the Zn / / Cu asymmetric battery of Test Example 8;

[0041] Fig. 9 This is a long-term cycle stability test diagram of the full battery of Test Example 9. DETAILED DESCRIPTION

[0042] In order to further illustrate the present invention, the aqueous zinc ion battery electrolyte and its preparation method and the aqueous zinc ion battery provided by the present invention are described in detail below.

[0043] Example 1

[0044] A) weighing o-phthalaldehyde powder according to a volume molar concentration of 1 mmol / L, and adding it into deionized water to dissolve it by ultrasonication (300W, 30min) until a clear solution is obtained;

[0045] B) Zinc sulfate was weighed at a molar concentration of 2 mol / L and ultrasonically dissolved (300 W, 1 h) in the above solution to prepare an aqueous zinc ion battery electrolyte with a high-efficiency electrolyte additive.

[0046] Example 2

[0047] A) weighing o-phthalaldehyde powder according to a volume molar concentration of 3 mmol / L, and adding it into deionized water to dissolve it by ultrasonication (300W, 30min) until a clear solution is obtained;

[0048] B) Zinc sulfate was weighed at a molar concentration of 2 mol / L and ultrasonically dissolved (300 W, 1 h) in the above solution to prepare an aqueous zinc ion battery electrolyte with a high-efficiency electrolyte additive.

[0049] Example 3

[0050] A) weighing o-phthalaldehyde powder according to a volume molar concentration of 5 mmol / L, and adding it into deionized water to dissolve it by ultrasonication (300W, 30min) until a clear solution is obtained;

[0051] B) zinc sulfate was weighed at a molar concentration of 2 mol / L and ultrasonically dissolved (300 W, 30 min) in the above solution to prepare an aqueous zinc ion battery electrolyte with a high-efficiency electrolyte additive.

[0052] Example 4

[0053] A) weighing o-phthalaldehyde powder according to a volume molar concentration of 10 mmol / L, and adding it into deionized water to dissolve it by ultrasonication (300W, 30min) until a clear solution is obtained;

[0054] B) zinc sulfate was weighed at a molar concentration of 2 mol / L and ultrasonically dissolved (300 W, 30 min) in the above solution to prepare an aqueous zinc ion battery electrolyte with a high-efficiency electrolyte additive.

[0055] Example 5

[0056] A) weighing o-phthalaldehyde powder according to a volume molar concentration of 10 mmol / L, and adding it into deionized water to dissolve it by ultrasonication (300W, 30min) until a clear solution is obtained;

[0057] B) zinc sulfate was weighed at a molar concentration of 1 mol / L and ultrasonically dissolved (300 W, 30 min) in the above solution to prepare an aqueous zinc ion battery electrolyte with a high-efficiency electrolyte additive.

[0058] Example 6

[0059] A) weighing o-phthalaldehyde powder according to a volume molar concentration of 10 mmol / L, and adding it into deionized water to dissolve it by ultrasonication (300W, 30min) until a clear solution is obtained;

[0060] B) zinc sulfate was weighed at a molar concentration of 3 mol / L and ultrasonically dissolved (300 W, 30 min) in the above solution to prepare an aqueous zinc ion battery electrolyte with a high-efficiency electrolyte additive.

[0061] Comparative Example 1

[0062] Zinc sulfate was weighed according to a volume molar concentration of 2 mol / L and ultrasonically dissolved (300 W, 30 min) in deionized water to prepare an aqueous zinc ion battery electrolyte without a high-efficiency electrolyte additive.

[0063] Comparative Example 2

[0064] Zinc sulfate was weighed according to a volume molar concentration of 1 mol / L and ultrasonically dissolved (300 W, 30 min) in deionized water to prepare an aqueous zinc ion battery electrolyte without a high-efficiency electrolyte additive.

[0065] Comparative Example 3

[0066] Zinc sulfate was weighed according to a volume molar concentration of 3 mol / L and ultrasonically dissolved (300 W, 30 min) in deionized water to prepare an aqueous zinc ion battery electrolyte without a high-efficiency electrolyte additive.

[0067] Comparative Example 4

[0068] A) Ether was weighed at a molar concentration of 5 mmol / L and added to deionized water and dissolved by ultrasonication (300 W, 30 min) until a clear solution was obtained;

[0069] B) Zinc sulfate was weighed at a molar concentration of 2 mol / L and ultrasonically dissolved (300 W, 1 h) in the above solution to prepare an aqueous zinc ion battery electrolyte with an ether electrolyte additive.

[0070] Electrolyte characteristic research and performance test experiment

[0071] Test Example 1

[0072] The aqueous zinc ion electrolytes obtained in Example 3 (5 mM o-phthalaldehyde, OPA-5 mM) and Comparative Example 1 (0 mM o-phthalaldehyde, OPA-0 mM) were used to perform EXAFS tests, and the EXAFS spectra of different electrolytes were obtained as shown in FIG. Figure 1 shown.

[0073] Figure 1 It shows that the Zn-O bonds in the EXAFS of the electrolytes obtained in Example 3 and Comparative Example 1 have the same radial distance and strength, indicating that the coordinating atoms of the zinc ions in the electrolyte are of the same type, and o-phthalaldehyde does not participate in the solvation structure of the zinc ions and will not change the properties of the electrolyte.

[0074] Test Example 2

[0075] The aqueous zinc ion electrolytes obtained in Example 3 (5 mM o-phthalaldehyde, OPA-5 mM), Example 4 (10 mM o-phthalaldehyde, OPA-10 mM), and Comparative Example 1 (0 mM o-phthalaldehyde, OPA-0 mM) were used as electrolytes to assemble Zn / / Zn symmetric cells for surface differential capacitance testing, and the results were obtained. Figure 2 Surface differential capacitance diagram shown.

[0076] Figure 2 The results show that the zinc negative electrode in the aqueous zinc ion electrolyte with o-phthalaldehyde additive has a smaller surface capacitance, which is caused by the larger volume of o-phthalaldehyde molecules compared with water molecules, proving the successful construction of the o-phthalaldehyde molecule-aggregated electrode interface layer at the zinc negative electrode interface.

[0077] Test Example 3

[0078] The aqueous zinc ion electrolytes obtained in Example 3 (5 mM o-phthalaldehyde, OPA-5 mM), Example 4 (10 mM o-phthalaldehyde, OPA-10 mM), and Comparative Example 1 (0 mM o-phthalaldehyde, OPA-0 mM) were used as electrolytes to assemble Zn / / Zn symmetric cells for Tafel tests, and the Tafel curves of different electrolytes were obtained as shown below. Figure 3 shown.

[0079] Figure 3 The results show that the OPA additive makes the aqueous zinc ion electrolyte have a higher corrosion potential and a smaller corrosion current. For example, in the electrolyte of Example 3 (OPA-5 mM), the corrosion current is 0.694 mA cm -2 , the corrosion potential is 0.045V; in the electrolyte of Comparative Example 1 (OPA-0mM), the corrosion current is 2.561mA cm -2, the corrosion potential is 0.035V; this proves that the zinc anode has better corrosion resistance in the electrolyte with o-phthalaldehyde additive.

[0080] Test Example 4

[0081] The aqueous zinc ion electrolytes obtained in Example 3 (5 mM o-phthalaldehyde, OPA-5 mM) and Comparative Example 1 (0 mM o-phthalaldehyde, OPA-0 mM) were used as electrolytes to assemble Zn / / Zn transparent batteries for in-situ optical microscopy testing. The cross-sectional evolution of the zinc negative electrode in different electrolytes was obtained as follows: Figure 4 shown.

[0082] Figure 4 It shows that in Example 3, ZnSO 4 During the 120-min deposition in the OPA electrolyte (OPA-5 mM), the Zn deposition was highly uniform and dense without protrusions or dendrites. 4 In the electrolyte (OPA-0mM), obvious protrusions appeared after only 30 minutes of deposition, and gradually developed into large dendrites within 120 minutes. In the absence of OPA regulation, the surface of the zinc negative electrode showed significant irregularity and porosity. The above results show that the aqueous zinc ion battery electrolyte described in the present invention guides the uniform deposition of zinc at the molecular aggregation electrode interface.

[0083] Test Example 5

[0084] The aqueous zinc ion electrolytes obtained in Example 3 (5 mM o-phthalaldehyde, OPA-5 mM) and Comparative Example 1 (0 mM o-phthalaldehyde, OPA-0 mM) were used as electrolytes to assemble Zn / / Zn symmetrically at 1 mA cm -2 , 1mA h cm -2 The zinc sheet was cycled for 100 cycles under the conditions of , and the surface was tested by scanning electron microscope after the cycle. Figure 5 shown.

[0085] Figure 5 It shows that in Example 3, ZnSO 4 / OPA electrolyte (OPA-5mM), after 100 cycles, an obvious layered structure appeared on the surface of the zinc negative electrode, and this layered deposition formed a dense and flat morphology. 4 In the electrolyte (OPA-0 mM), zinc nucleates randomly and grows into large protrusions that are intertwined with the disordered fibers on the separator.

[0086] Test Example 6

[0087] The aqueous zinc ion electrolytes obtained in Example 3 and Comparative Example 1 were used as electrolytes to assemble Zn / / Zn symmetric cells at 1 mA cm -2 , 1mA h cm -2 The cycle stability test was carried out under the conditions of Figure 6 shown.

[0088] Figure 6 It shows that in Example 3, ZnSO 4 / OPA electrolyte (OPA-5mM), the battery was at 1.0mA cm -2 The current density and 1.0 mA h cm -2 The capacity shows excellent cycle stability, which can be cycled for more than 2200 hours, which is better than that of pure ZnSO in Example 1. 4 The results show that the zinc negative electrode OPA-enriched interface constructed by the electrolyte of the present invention has good cycle stability, high electrochemical reversibility and durability.

[0089] Test Example 7

[0090] The aqueous zinc ion electrolyte with ether electrolyte additive obtained in Comparative Example 4 was used as the electrolyte to assemble a Zn / / Zn symmetric cell at 1 mA cm -2 , 1mA h cm -2 The cycle stability test was carried out under the conditions of Figure 7 shown.

[0091] Figure 7 It shows that in Comparative Example 4, ZnSO 4 / C 4 H 10 O electrolyte (C 4 H 10 O-5mM), the battery was at 1.0mA cm -2 The current density and 1.0 mA h cm -2 The capacity can be cycled for 500 hours, which is better than the pure ZnSO in Example 1. 4 However, the ZnSO 4 / OPA electrolyte (OPA-5mM) has poor cycle stability. This shows that the zinc negative electrode OPA enriched interface constructed by the electrolyte of the present invention has good cycle stability, high electrochemical reversibility and durability, and is better than ether at the same addition concentration. Test Example 8

[0092] The aqueous zinc ion electrolytes obtained in Example 3 and Comparative Example 1 were used as electrolytes to assemble Zn / / Cu asymmetric batteries for reversibility study. -2 The current density and 2.0 mAh cm -2 The capacity was electrodeposited onto a copper substrate and then charged at 0.5 V to Zn 2+ / Zn cut-off voltage to remove zinc. The results are as follows Figure 8 As shown, the ZnSO of Example 3 4 / OPA electrolyte (5mM o-phthalaldehyde, OPA-5mM) enables the Zn / / Cu battery to operate stably for 1000 cycles with an initial Coulombic efficiency of 88.18% and an average Coulombic efficiency of 99.54%. 4 The electrolyte (0 mM o-phthalaldehyde, OPA-0 mM) can only maintain 53 cycles with an initial coulombic efficiency of 80.35%. Therefore, the battery assembled with the zinc negative electrode of Example 3 has higher reversibility. This enhanced reversibility originates from the smaller nucleation radius on the OPA-enriched zinc interface, which promotes the uniformity and refinement of zinc grains during the deposition process.

[0093] Test Example 9

[0094] The aqueous zinc ion electrolytes obtained in Example 3 and Comparative Example 1 were used as electrolytes to assemble full batteries for practical research. The positive electrode material was selected as vanadium pentoxide (NVO) intercalated with ammonium ions. The positive electrode preparation process was as follows: the active materials NVO, super activated carbon, carbon nanotubes and polyvinylidene fluoride (PVDF) were mixed in NMP solvent at a weight ratio of 7:1.5:0.5:1 respectively. In the CR2032 button cell configuration, a complete battery was assembled using NVO positive electrode, zinc negative electrode and GF / D glass fiber separator. At 0.2-1.6V (with Zn 2+ / Zn relative) voltage range, the long-term cycling stability was evaluated using the LAND battery testing system.

[0095] The results are as follows Fig. 9 As shown, at 0.1A g -1 After pre-activation for 5 times at a current density of 5.0A g -1 After 1000 cycles at a current density of 2.5 Å, the capacity retention rate of the battery with OPA additive was 233.5 mA h g -1 In contrast, the battery without additives had a lower capacity retention rate of only 147.8 mA hg -1 .

[0096] In summary, it is shown that the high-efficiency electrolyte for aqueous zinc ion batteries prepared by the present invention can significantly inhibit the growth of dendrites and corrosion of aqueous zinc ions, thereby improving the cycle performance of zinc ion batteries.

[0097] The above description is only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. An aqueous zinc ion battery electrolyte, characterized in that Including phthalaldehyde and zinc salts.

2. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The concentration of o-phthalaldehyde in the battery electrolyte is 1-20 mmol / L.

3. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The concentration of zinc salt in the battery electrolyte is 1-3 mol / L.

4. The aqueous zinc ion battery electrolyte according to claim 3, characterized in that The zinc salt is selected from one or more of zinc sulfate, zinc acetate, zinc perchlorate and zinc trifluoromethanesulfonate.

5. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The electrolyte also includes deionized water.

6. The method for preparing an aqueous zinc ion battery electrolyte according to any one of claims 1 to 5, characterized in that: The aqueous solution of o-phthalaldehyde and zinc salt are evenly mixed to obtain the aqueous zinc ion battery electrolyte.

7. The preparation method according to claim 6, characterized in that: The mixing is selected from ultrasonic mixing; The power of the ultrasonic mixing is 200-400W; The ultrasonic mixing time is 30-100 min.

8. An aqueous zinc ion battery, characterized in that: The invention comprises the aqueous zinc ion battery electrolyte described in any one of claims 1 to 5 or the aqueous zinc ion battery electrolyte prepared by the preparation method described in claim 6 or 7.

9. The aqueous zinc ion battery according to claim 8, characterized in that: The aqueous zinc ion battery also includes a vanadium pentoxide positive electrode intercalated with ammonium ions, a metal zinc negative electrode and a glass fiber separator.

10. Application of the aqueous zinc ion battery according to claim 8 or 9 in new energy vehicle power batteries, stationary energy storage fields, and 3C consumer electronic products.